Competencia económica en mercados digitales: la experiencia en México - García Santos Coy, Luis Gerardo; Kargl Pavía, Jorge; Esparza Fregoso, Regina (Pontificia Universidad Católica del Perú, 2020)
Digital platforms are changing the world, from the way we communicate to the way we commercialize products and services. Antitrust regulators are facing new challenges as they review entirely new and unprecedented markets with particular rules and dynamics. In Mexico, both antitrust authorities (the Federal Economic Competition Commission and the Federal Institute of Telecommunications) have suggested different interpretations regarding a jurisdictional assessment for digital markets, to the extent that it has been necessary to involve Federal Courts. Particularities of multiple-sided markets, big data, indirect network effects, multi-homing and the different conception of market power in digital markets have required a new approximation by antitrust authorities, both regarding merger control and in the investigation and prosecution of anticompetitive behavior.

Las plataformas digitales están cambiando el mundo, desde la forma en que nos comunicamos hasta la manera de comercializar bienes y servicios. Los reguladores de competencia económica se enfrentan a nuevos retos al analizar mercados totalmente novedosos con reglas y dinámicas propias. En México, las dos autoridades en materia de competencia económica en México (Comisión Federal de Competencia Económica e Instituto Federal de Telecomunicaciones) han sostenido distintas interpretaciones en relación con la jurisdicción para analizar asuntos relacionados con los mercados digitales, al grado en que se ha requerido la intervención del Poder Judicial de la Federación. Las particularidades de los mercados de múltiples lados, el papel del big data, los efectos indirectos de red, el multi-homing y la distinta concepción del poder de mercado en los mercados digitales requieren una nueva aproximación por parte de las autoridades en materia de competencia, tanto para el control de concentraciones, como para la investigación y persecución de prácticas anticompetitivas.
Economic competition (antitrust) in digital markets: The experience in Mexico
Keywords: Plataformas digitales; Mercados digitales; México; Cofece; IFT; https://purl.org/pe-repo/ocde/ford#5.05.01